Az Európai Unió intézményrendszere és működése, a hazai környezetvédelmi infrastruktúra-fejlesztési projektek szemszögéből - Szabó, Ferenc (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The cooperation of the highly developed western European countries has led to significant success, mainly after the establishment of the European Union. The original goals, peace, prosperity and human rights were assured. However, the inner conflicts of the system have been producing operational difficulties time to time. One of the main goals of the "Lisbon Process 2000" was to eliminate these operational problems, in order to strengthen competitiveness. The accession to the EU meant great opportunities to the new members, first of all in the field of environmental infrastructure development. The EU support and funds made it possible to the eastern European countries to reach the level of the h developed counties in a few years. But it's clear that the support systems are difficult, the regulations and conditions are very strict. On one hand, an effective national level regulation and management has to be required, on the other hand the professionalism of the beneficiaries has to be increased in the near future.